“Now What?”: Exploring Newcomer Youth’s Transition from High School to Postsecondary Education - Gallucci, Alissa; Kassan, Anusha (Canadian Journal of Counselling and Psychotherapy, 2019)
For newcomer youth (i.e., those who have recently migrated to Canada with their families), high school integration has a marked influence on postsecondary preparation. This descriptive phenomenological study aimed to answer the following research question: How do newcomer youth’s experiences in high school impact their transition to postsecondary education? In total, 10 participants, ages 18 through 24, completed in-depth qualitative interviews. Data analysis revealed 5 structures: 3 related to decision-making processes (i.e., high school influence, personal ambitions, and family factors), and 2 centred on experiences in postsecondary education (i.e., areas of growth and postsecondary challenges). Results point to the need for increased support for newcomer youth both in high school and university.